Green Urbanism in Asia: The emerging green tigers - Newman, Peter; Matan, Annie (World Scientific Publications, 2013)
The world is facing an age of scarcity which will challenge all cities to reduce their resource footprint, especially carbon, improve biodiversity and at the same time continue to create economic opportunities and liveable places. This is green urbanism. Asian urban growth is leading the world in the rapidity of its change but how is it doing on green urbanism? This book finds emerging innovations and first signs of green urbanism in Asia and suggests they may be the guiding light for the rest of the world. The authors highlight seven archetypal cities exhibiting green urbanism: the renewable energy city, the bioregional carbon neutral city, the distributed city, the biophilic city, the eco-efficient city, the place-based city and the sustainable transport city. The book is a must-read for all who are concerned with the future of our cities as it instills hope that a greener urban future is possible.